Dynamic Sonographic Visualization of an Occult Posterior Lateral Meniscocapsular Separation: A Case Report. Issue 11 (4th April 2018) - Schroeder, Allison; Musahl, Volker; Urbanek, Christopher; Onishi, Kentaro
Abstract: Meniscocapsular separation describes detachment of the meniscus from the knee joint capsule. Diagnosis is challenging with conventional examination and imaging methods. We report a case of an 18‐year‐old female softball catcher with unrevealing magnetic resonance imaging despite continued left knee locking and discomfort with deep squatting. Meniscocapsular separation was revealed only on dynamic sonographic examination, where knee flexion revealed a 3.1‐mm gap that developed between the capsule and peripheral meniscus. Arthroscopy confirmed the sonographic findings, and repair resulted in complete resolution of symptoms. This case highlights the utility of dynamic diagnostic sonography in a rare case of posterior lateral meniscocapsular separation. Level of Evidence: V